CERDASBELAJAR : MEDIA PEMBELAJARAN SEKOLAH DASAR BERBASIS ANDROID UNTUK MENDUKUNG PEMBELAJARAN DARING - Asril Adi Sunarto; Elnawati Elnawati (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2021)
Covid19 pandemic is forcing the world to adapt to a new life. One of the impacts is the educational world. Distance learning from home or online learning is indeed one of the learning solutions with this Covid-19 condition. Problems arise when not all students and teachers can carry out learning at home optimally. Various obstacles faced such as mobile phones, internet access, learning media, interesting learning material content, and others. Teachers realize that audio-visual content is indeed more attached and easier for students to digest when delivering a material. So what is happening at this time both from the side of students and teachers becomes a dilemma. Therefore, we need a way so that what students and teachers complain about having internet access and learning media problems can be resolved, one of which is by developing learning applications along with educational content for elementary school students based on audio-visuals to support learning both outside the network (offline). as well as in the network (online). We call the application the CerdasBelajar application. As a result, the CerdasBelajar application has been published on Google Playstore and stored as many as 34 learning videos, material discussion, practice questions, and arithmetic gamers and can be installed for free.